The Influence of Interactive Multimedia on Students’ Motivation in Learning Islamic Values - Buchori, Ahmad; Laili, Izzatul; Tambunan, Amalia Hikmayanti; Santosa, Tomi Apra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines The Influence of Interactive Multimedia on Students’ Motivation in Learning Islamic Values, focusing on how digital learning tools can enhance learners’ engagement and motivation in religious education. Utilizing a quasi-experimental design, the research compares students who received instruction through interactive multimedia such as animations, quizzes, and visual simulations with those who learned through conventional teaching methods. Data were collected using a validated motivation questionnaire and analyzed through descriptive and inferential statistics to determine the significance of differences between groups. The findings indicate that interactive multimedia has a positive and significant effect on students’ motivation, particularly in increasing attention, fostering interest, and stimulating self-directed learning in the context of Islamic values education. These results highlight the potential of technology-enhanced learning environments to support more meaningful and affective religious learning experiences. The study concludes that integrating interactive multimedia into Islamic education can serve as an effective pedagogical innovation to promote student motivation and improve the overall quality of learning outcomes.